2014
DOI: 10.1111/1541-4337.12072
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Methods in Food Safety Microbiology: Interpretation and Implications of Nucleic Acid Detection

Abstract: Because of increasing demand for rapid results, molecular techniques are now applied for the detection of microorganisms in foodstuffs. However, interpretation problems can arise for the results generated by molecular methods in relation to the associated public health risk. Discrepancies between results obtained by molecular and conventional culture methods stem from the difference in target, namely nucleic acids instead of actively growing microorganisms. Nucleic acids constitute 5% to 15% of the dry weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 216 publications
(171 reference statements)
1
45
0
Order By: Relevance
“…paratuberculosis DNA was only mildly degraded at such high thermal treatments, resulting in higher C T values post-DSI. Our findings confirm previous reports in which it was shown that DNA can withstand thermal degradation to yield positive PCR results (43,44). More importantly, the qPCR signal obtained post-DSI may explain the higher M. avium subsp.…”
Section: Discussionsupporting
confidence: 91%
“…paratuberculosis DNA was only mildly degraded at such high thermal treatments, resulting in higher C T values post-DSI. Our findings confirm previous reports in which it was shown that DNA can withstand thermal degradation to yield positive PCR results (43,44). More importantly, the qPCR signal obtained post-DSI may explain the higher M. avium subsp.…”
Section: Discussionsupporting
confidence: 91%
“…However, in some cases, EMA and PMA could also diffuse into living bacterial cells with intact membranes (14). On the other hand, RNA is considered a more useful target for viable bacteria even though rRNA molecules remain available for detection after bacterial death for some generally not predictable time (14). Moreover, RNA should be considered a more informative target than DNA, as rRNA can be proportionally more abundant in microbial cells than DNA copies, and this could lead to a more detailed picture of the matrix analyzed (15).…”
mentioning
confidence: 99%
“…To avoid this bias, several authors suggested the use of treatments with propidium monoazide (PMA) or ethidium monoazide (EMA) prior to DNA extraction to detect or quantify viable microorganisms. However, in some cases, EMA and PMA could also diffuse into living bacterial cells with intact membranes (14). On the other hand, RNA is considered a more useful target for viable bacteria even though rRNA molecules remain available for detection after bacterial death for some generally not predictable time (14).…”
mentioning
confidence: 99%
“…Most of these pathogens are not easily individuated by using traditional approaches, and metagenomic methods have been adopted, mainly using 16s rDNA or 26s rDNA gene sequencing [16,17]. These approaches have a growing importance also in the authentication product activity [18].…”
Section: Food Qualitymentioning
confidence: 99%